POSSIBLE ERRORS OF CALCULATIONS OF LOSSES OF THE ELECTRIC POWER ON SHOP INDUSTRIAL NETWORKS - E. I. Gracheva; A. N. Alimova (Известия высших учебных заведений: Проблемы энергетики)
In the article it is devoted the analysis and researches of origins and values of possible errors from not accounting of the main defining characteristics when calculating losses of the electric power on shop networks of a low tension. It is proved that in case of determination of losses of the electric power in lines of shop networks it is necessary to consider influence of the following parameters of the equipment: the heating of conductors caused by passing of current of loading through conductors and ambient temperature; resistance of contact joints of switching devices and their number; type of the load graph; ambient temperatures. The diagram of a shop network and daily load graphs of customers of one of the enterprises is researched. Errors of calculations of losses of the electric power are calculated and the analysis of influence of parameters of the equipment on value of losses of the electric power is carried out. The absence of reliable information about elements of shop networks of a low tension and not accounting of the determining leads to an error 5 - 80% in case of computation of losses of the electric power in the systems of industrial electrical power supply.